PSST: Enabling Blind or Visually Impaired Developers to Author Sonifications of Streaming Sensor Data - Potluri, Venkatesh; Thompson, John; Devine, James; Lee, Bongshin; Morsi, Nora; Halleux, Jonathan "Peli" de; Hodges, Steve; Mankoff, Jennifer (ACM UIST, 2022)
We present the first toolkit that equips blind and visually impaired (BVI) developers with the tools to create accessible data displays. Called PSST (Physical computing Streaming Sensor data Toolkit), it enables BVI developers to understand the data generated by sensors from a mouse to a micro:bit physical computing platform. By assuming visual abilities, earlier efforts to make physical computing accessible fail to address the need for BVI developers to access sensor data. PSST enables BVI developers to understand real-time, real-world sensor data by providing control over what should be displayed, as well as when to display and how to display sensor data. PSST supports filtering based on raw or calculated values, highlighting, and transformation of data. Output formats include tonal sonification, nonspeech audio files, speech, and SVGs for laser cutting. We validate PSST through a series of demonstrations and a user study with BVI developers.